الدّراسات الثّقافيّة واستعادة الصّوت المهمَّش رواية "نهاية الصّحراء" لسعيد خطيبي أنموذجا - رابطي, أحمد; كحلوش, فتيحة (جامعة الوادي - University of Eloued, 2023)
ملخّص: نسعى من خلال دراستنا الموسومة بـ: "الدّراسات الثّقافيّة واستعادة الصّوت المهمَّش-رواية نهاية الصّحراء لسعيد خطيبي أنموذجا-" إلى التّعريف بالدّراسات الثّقافيّة، والتّطرّق إلى الإرهاصات الفكريّة الّتي قامت عليها، والآليات القراءائيّة الجديدة، وكشف الأسس والأهداف الّتي تسعى إليها في سبيل إحلال تلك الثّقافة البديلة الّتي تعيد إلى لآخر/المهمَّش صوته المسلوب، وخطاباته المغتصبة. وفي سبيل ذلك ولجنا إلى متن الرّواية، حيث تجلّت فيها صورة الأنثى كنسق يحمل مضمرات ثقافيّة استلابيّة، مارسها عليها العنصر الذّكوريّ كطاغية يقودها إلى التّشظّي، والّذي زادت من حدّته عوامل سلبيّة ترسّخت في البيئة العربيّة، وتجذّرت في ذهنية المرأة، فجعلتها تؤمن بدونيتها في حدود هذا الفضاء، أمام سلطة الطّاغية الذّكوريّ. الكلمات المفتاحيّة: رواية نهاية الصّحراء لسعيد خطيبي؛ الدّراسات الثّقافية؛ الطّاغية؛ الهيمنة. Abstract: Through our study titled: "Cultural Studies and the Restoration of the Marginalized Voice - Saeed Khatibi's End of the Desert Novel as an Example -" we seek to define cultural studies, address the intellectual precursors on which they are based, the new reading mechanisms, and reveal the foundations and goals that it seeks to achieve in order to establish that culture. The alternative that restores to the other/marginalized his stolen voice and usurped speeches. In order to achieve this, we entered the body of the novel, where the image of the female was manifested as a pattern that carries cultural connotations that alienated her, which was practiced on her by the male element as a tyrant leading her to fragmentation, which was aggravated by negative factors that took root in the Arab environment, and took root in the mentality of women, making her believe in her inferiority within the limits of this. Space before the power of the male tyrant. key words: The End of the Desert novel by Saeed Khatibi; cultural studies; Tyrant; domination.
Article
Keywords: رواية نهاية الصّحراء لسعيد خطيبي؛ الدّراسات الثّقافية؛ الطّاغية؛ الهيمنة; The End of the Desert novel by Saeed Khatibi; cultural studies; Tyrant; domination